Diversifying the Teaching Profession Dimensions, Dilemmas and Directions for the Future - Keane, Elaine; Heinz, Manuela; Mc Daid, Rory (Routledge Research in Educational Equality and Diversity, 2023)
This edited volume is about diversifying the teaching profession. It is unique in its inclusion of multiple dimensions of diversity; its chapters focus on a wide range of under-represented groups, including those from lower socio-economic groups, Black and minority ethnic groups, migrants, the Travelling community, the Deaf community, the LGBTQI+ community and those of mature age. The book includes contributions from Australia, England, Iceland, Portugal and Scotland, as well as a number of chapters from the Irish context, mostly emanating from projects funded under Ireland's Higher Education Authority's Programme for Access to Higher Education (PATH): Strand 1-Equity of Access to Initial Teacher Education. The book also critically engages the rationale for diversifying the profession, arguing not only that representation still matters, but also that ultimately teacher diversity work needs to encompass system transformation to achieve a diverse, equitable and inclusive teaching profession.